PSXIII-40 Superovulation and oocyte recovery rates in CIDR synchronized goats treated with PGF2α, FSH and GnRH during breeding season. (5th December 2019) - Singh, Mahipal; Park, Ki-Eun; Tyler, William; McCommon, George; Bhanu, Telugu; Knight, Miranda; Gilespie, Ann; Ma, Xiaoling; Powel, Ann; Donovan, David; Ramsay, Timothy
Abstract: Embryo transfer is an advanced technology and has great potential in increasing desired livestock without physical boundaries. Multiple embryos can be produced in-vitro or in-vivo using semen from desired males. Early stage embryos (zygotes) are also ideal tools for genome-editing to alter the desired traits. However, the small number of mature oocytes produced each cycle is a major limitation of this technology. Scientists have used drugs to stimulate follicles to increase the number of oocytes/embryos. Extra oocytes/embryos produced can be cryopreserved or shipped to distant locations, to disseminate genetics around the world, at a fraction of cost. Embryos produced from superovulated animals can be transferred in recipient does, to produce desired number of animals. The goal of this study was to estimate the rate of ovulation and oocyte recovery after drug induced superovulation in goats. Eight cycling does were synchronized for estrus, using intravaginal CIDR dispensers, for 11 days during natural breeding season. Each doe was superovulated with a total of 200 mg of pFSH administered intramuscularly in 6 dosages (50 mg, 30 mg, and 20 mg given twice a day at 12 h interval) starting 48 h prior to CIDR removal. Each doe also received 8 mg of PGF2α, 24 h prior to CIDR removal, and 86 µg of GnRH 24 h after CIDR removal. The superovulatory response was evaluated by counting corpus luteum (CL) on each ovary after 48 h of GnRH injection. The ovulated oocytes were recovered surgically from oviducts by flushing with TL Hepes medium. Mean and standard deviation of CL calculated was 10.86±6.34 and 11.67±6.15 CL per doe (n = 8) in left and right ovaries, respectively. Similarly, mean and SD of mature oocytes recovered was 7.67±6.50 and 9.67±5.10 for left and right oviducts, respectively. Average percent recovery of oocytes was 71.23 % / doe.